(untitled) (Modern education and development, 2025)
World literature encompasses a vast array of literary works from different cultures, historical periods, and languages. It serves as a bridge between societies, allowing readers to explore diverse perspectives, traditions, and philosophies. This article examines the concept of world literature, its historical evolution, and its role in fostering global understanding and cultural exchange.